Pharmacological Actions, Molecular Mechanisms, Pharmacokinetic Progressions, and Clinical Applications of Hydroxysafflor Yellow A in Antidiabetic Research. (13th December 2021) - Zhang, Xilan; Shen, Dayue; Feng, Yating; Li, Yuanping; Liao, Hui
Abstract : Hydroxysafflor yellow A (HSYA), a nutraceutical compound derived from safflower ( Carthamus tinctorius ), has been shown as an effective therapeutic agent in cardiovascular diseases, cancer, and diabetes. Our previous study showed that the effect of HSYA on high-glucose-induced podocyte injury is related to its anti-inflammatory activities via macrophage polarization. Based on the information provided on PubMed, Scopus and Wanfang database, we currently aim to provide an updated overview of the role of HSYA in antidiabetic research from the following points: pharmacological actions, molecular mechanisms, pharmacokinetic progressions, and clinical applications. The pharmacokinetic research of HSYA has laid foundations for the clinical applications of HSYA injection in diabetic nephropathy, diabetic retinopathy, and diabetic neuropathy. The application of HSYA as an antidiabetic oral medicament has been investigated based on its recent oral delivery system research. In vivo and in vitro pharmacological research indicated that the antidiabetic activities of HSYA were based mainly on its antioxidant and anti-inflammatory mechanisms via JNK/c-jun pathway, NOX4 pathway, and macrophage differentiation. Further anti-inflammatory exploration related to NF- κ B signaling, MAPK pathway, and PI3K/Akt/mTOR pathway might deserve attention in the future. The anti-inflammatory activities of HSYA related to diabetes and diabetic complications will be a highlight in our following research.